The Health Benefits of Probiotics - Yap, Wei Boon; Sujang, Rina (penerbit ukm, 2014)
There has been a signifi cant increase in research on probiotics-associated health benefi ts in the last 20 years. Many studies carried out in vitro and clinically show that consumption of probiotics inhibits the growth of pathogenic microorganisms. Furthermore, the consumption of probiotics also enhances the host immune response and decreases the levels of carcinogenesis-inducing enzymes. These positive outcomes have led to the use of probiotics in prevention and treatment of infectious diseases like bacterial or antibiotic associated diarrhea, chronic infl ammatory bowel diseases and colon cancer. This review summarises literature pertaining to mechanistic actions of probiotics in improving the well-being of hosts.